Daerah-Daerah Gundul dan Dampaknya - Wehelmina Mauleti; Melki Imamastri Puling Tang; Jon A. Lalang Yame; Tuwentisri Maukay; Selfince Atamau; Steven Weni; Tofilus Ataruli; Orpa Etidena (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this study is to find out: (1) deforested areas in Alor district, (2) The impact that occurs due to deforested areas. The method used in this study is descriptive analysis, which is a way to describe and analyze symptoms and situations that are part of the problem under study. The results showed that the length of this study that made the subject was Manimau Hill which had different conditions from other hills. Where the hill is deforested so that there is not a single tree growing around the area. The number of research data sources is based on qualitative research considerations that are more concerned with a lot of information than the number of informants. (2) The impact of deforested forests on the environment and society are: disrupting the water cycle, forest fires, death of flora and fauna, reduced water supply, global warming low air quality, loss of livelihoods and loss of natural resources.